2023
DOI: 10.3390/ijfs11010023
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Big Data Analytics Capabilities on Firm Performance in the Malaysian Banking Sector

Abstract: Banks’ primary goal is to gain profit for survival and to thrive. Therefore, they have to take various measures, such as data analysis, to maintain their sustainable competitiveness. Along with the rapid development of information technology, big data analytics capabilities (BDAC) is considered essential for banks in the highly dynamic market. To gain an in-depth understanding of the economic importance of BDAC in the banking sector in Malaysia, this research examines the relationship between BDAC and firm per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…The main characteristic of big data can be summarized in "5Vs", including volume, variety, velocity, veracity, and value ( Wamba et al, 2017 ). However, big data itself barely has crucial business values without suitable analytical tools ( Aziz et al, 2023 ). Thus, it is necessary for an organization to perform big data analytics (BDA).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristic of big data can be summarized in "5Vs", including volume, variety, velocity, veracity, and value ( Wamba et al, 2017 ). However, big data itself barely has crucial business values without suitable analytical tools ( Aziz et al, 2023 ). Thus, it is necessary for an organization to perform big data analytics (BDA).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, prior research measures firm performance by two separate constructs, namely market performance and operational performance ( Gupta and George, 2016 , Gupta et al, 2018 ). Based on the literature, market performance measures a commercial organization's actual outcomes (e.g., market share and new markets), and operational performance refers to an organization's productivity (e.g., profits and return on investment) ( Aziz et al, 2023 , Liu et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that it has a positive impact on customer satisfaction. Similarly, Aziz and Long (2023) mentioned that banks are more likely to grow their profitability by targeting the right consumers, improving customer experience, maintaining solid customer relationships, and lowering customer acquisition/retention costs.…”
Section: The Impact Of Digital Transformation On the Customer Experie...mentioning
confidence: 99%
“…In addition, there needs to be more research in Malaysia's context discussing the impact of digital transformation on customer experience. Malaysia's banking sector is regarded as stable, yet it is still expanding and dealing with rapidly changing market challenges (Aziz & Long, 2023). To remain competitive, banks try to provide clients with innovative products/services (e.g., mobile payment and facial recognition) and implement organizational changes that improve value Digital Customer Experiences: A Multiple Case Study Approach of Malaysia Financial Institutions creation and customer experience optimization (Cegarra-Navarro et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Q.ai, a robo-advisory app, uses AI and big data to provide customized portfolio recommendations and maximize returns on investments [33]. Banks also use big data analytics to study consumption patterns and customer behavior [34,35]. Similarly, health insurance companies use data from wearable technologies to provide superior customer service and product innovations [36], and some insurance companies track driving data to reward safe driving [37].…”
Section: Big Datamentioning
confidence: 99%